PEMBERIAN BEKICOT (Achatina fulica) TERHADAP PERTUMBUHAN IKAN KAKAP PUTIH (Lates calcarifer) - Nadju, Marlen Brilian Riwu; Ratoe Oedjoe, Marcelien Dj; Liufeto, Franchy Ch (Nusa Cendana University, 2025)
This research was carried out at BBIP Tablolong, Kupang Regency for 60 days. The aim of this research was to determine the effect of feeding snails (Achatina fulica) on the growth of white snapper (Lates calcarifer). The design used was RAL with 4 treatments and 3 repetitions, namely (A) f999 pellets 5% of the biomass weight (control), (B) snails 5% of the biomass weight, (C) snails 10% of the biomass weight, (D) snails 15% of the biomass weight. The parameters measured in this study are Absolute Weight Growth, SGR, SR, FCR, Feed Efficiency. The research results prove that treatment (B) Snails 5% of biomass weight is the best dose for the growth of white snapper with an absolute weight growth rate of 8.3 g, SGR reaching 0.048%g/day, SR of white snapper 90%, FCR 1.36 g, and feed efficiency value reaching 73.44%. Keywords: Snail, sea bass, growth